MODERN PROFESSIONAL QUALITIES IN FUTURE TECHNOLOGICAL EDUCATION TEACHERS AND THEIR OWN RANGE OF VIRTUAL TECHNOLOGIES - B.B.Umrzaqov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the modern professional qualities and virtual technologies in the teachers of future technological education.